Field efficacy of biorational and chemical insecticides against mango leaf hoppers (Amritodus atkinsoni and Idioscopus spp.) - SINGH, SANDEEP; SANDHU, RAJWINDER KAUR; SHARMA, RAKESH KUMAR; KAUR, PRABHJOT; MAKKAR, GURPREET SINGH; RANDHAWA, HARPAL SINGH (The Indian Journal of Agricultural Sciences, 2022)
Mango hopper is an important pest of mango that causes severe losses in yield and lower quality of fruit. The objective of the study was to investigate the susceptibility of mango hopper to the selected chemical and botanical insecticides and to find out the efficacy of different concentrations of selected insecticides/botanicals in controlling the mango hopper in the field conditions. Field experiments were conducted at four locations of Punjab, viz. Gurdaspur (Regional Research Station), Hoshiarpur [Government Garden and Fruit Nursery, Khiala Bulanda; FRS, Gangian; Jhandia Kalan (Ropar)] to evaluate different botanicals and chemicals along with Malathion 50 EC as check insecticide during 2019–21. Results indicated that lambda-cyhalothrin 5 ec @1.0 ml/l, imidacloprid 17.8 SL @0.4 ml/l, deltamethrin 2.8 ec @0.5 ml/l, thiamethoxam 25 wg @0.1 g/l, dimethoate 30 ec @1.65 ml/l, buprofezin 25 sc @2.0 ml/l, oxydemeton methyl 25 ec @1.0 ml/l and malathion 50 ec @1.5 ml/l were found significantly effective against mango leaf hoppers with reduction in population from 90–60%. PAU homemade neem extract @14 ml/l and PAU homemade dharek extract @4 ml/l resulted in 28–80% reduction, respectively. These wide options will help the farmers for opting wide range of insecticides and botanicals for need based spraying of these insecticides instead of schedule sprayings.